EFEKTIFITAS PENERAPAN DIVERSI TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA DALAM SISTEM PERADILAN PIDANA ANAK TAHUN 2025 (STUDI PENELITIAN DI KABUPATEN BIREUEN) - Sudana Bambang Suganda; Muhammad Hatta; Marlia Sastro (Suloh: Jurnal Fakultas Hukum Universitas Malikussaleh, 2026)
The effectiveness of law in legal action or reality can be known if someone states that a legal rule has succeeded or failed to achieve its objectives, then it is usually known whether its influence has succeeded in regulating certain attitudes or behaviors so that they are in accordance with its objectives or not. The effectiveness of law means that the effectiveness of law will be highlighted from the objectives to be achieved, namely the effectiveness of law. One of the efforts that is usually made so that society complies with legal rules is to include its sanctions. The research method used in this thesis research is empirical legal research. This empirical legal research is also often referred to as sociological legal research or field research, which starts from primary data, namely data obtained directly from the community as the first source through field research activities. Primary data is obtained through observation and interview activities. Based on the results of research on the effectiveness of implementing diversion for children who commit crimes in the juvenile criminal justice system, it can be implemented well, even quite a few cases have been successfully diverted, although there are still cases that fail to be diverted because both parties do not agree, so it can be said that diversion has failed, but it can be concluded that diversion is one of the effective ways that can be done in resolving children's cases. It is recommended that law enforcement efforts for children's cases be more assertive and provide a deterrent effect so that it can reduce crimes committed by children, and several factors must also be given more attention, both from parents, the child's social environment, and a strong faith must be instilled in children so that children can protect themselves from the desire to commit crimes that should not be committed by adults or even the children themselves.